2022
DOI: 10.1016/j.jbc.2022.101713
|View full text |Cite
|
Sign up to set email alerts
|

The tetrameric structure of Plasmodium falciparum phosphoglycerate mutase is critical for optimal enzymatic activity

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…During the last years (2019-2022), several studies [14][15][16][17][18][19][20][21] were published discussing new approaches to identify novel drug targets for Plasmodium spp. Stanway et al [14] hypothesized that identifying genes encoding the high metabolic activities behind rapid development of a single sporozoite (invading the liver) into thousands of daughter-merozoites (invading RBCs) should reveal several potential drug targets.…”
Section: Drug Targets In Plasmodium Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last years (2019-2022), several studies [14][15][16][17][18][19][20][21] were published discussing new approaches to identify novel drug targets for Plasmodium spp. Stanway et al [14] hypothesized that identifying genes encoding the high metabolic activities behind rapid development of a single sporozoite (invading the liver) into thousands of daughter-merozoites (invading RBCs) should reveal several potential drug targets.…”
Section: Drug Targets In Plasmodium Sppmentioning
confidence: 99%
“…The study characterized PfPGM1 structure that revealed its existence in tetramer form, and in-depth oligomerization analysis showed that this tetramerization contributed to the optimal enzymatic function in vitro, and in vivo. Understanding PGM enzymatic mechanism of action might provided a promising strategy to design and develop a specific inhibitor as novel antimalarial drug [21] .…”
Section: Drug Targets In Plasmodium Sppmentioning
confidence: 99%